Microwave engineering [4th ed.] - Pozar, David M. (Hoboken: Wiley, 2012)
Microwave Engineering is a comprehensive book for undergraduate students of Electronics and Communications and Computer Science Engineering. The book comprises chapters on electromagnetic theory, transmission line theory, microwave network analysis, microwave resonators, microwave filters, microwave amplifier design, and oscillators and mixers. In addition, the book consists of new and updated material on wireless communications systems, along with several detailed diagrams and illustrations to understand the concepts better. This book is indispensable for engineering students preparing for competitive exams like Graduate Aptitude Test in Engineering.
Keywords: Microwaves; Microwave devices; Microwave circuits